Abo and Rh Blood Groups Distribution in Hemophilia and Anti Hiv Positive Individuals - D.D. FARHUD (Tehran University of Medical Sciences, 1987)
A group of Iranian patients suffering from Factor VIII deficiency (Hemophilia A) and treated with contaminated coagulation factor (imported), became seropositive as determined by ELISA method. Sixty of these individuals, which were available, were studied for ABO distribution. The B blood group in anti HIV pos. individuals (13.33%) shows a significant decrease in comparison with the total (1504) of factor VIII hemophilia (21.87%). Statistical analysis of ABO distribution in anti HIV Pos. compared with hemophilia A and the control group showed x2 values of 6.86(0.10 > p>0.05) and 10.21(0.02> P >0.01) respectively.